Detection of Multiple Sapovirus Genotypes and Genogroups in Oyster-Associated Outbreaks - Iwata, Hiroyuki; Akiyama, Miho; Noda, Mamoru; Takeda, Naokazu; Nakagawa-Okamoto, Reiko; Nishio, Osamu; Oka, Tomoichiro; Arita-Nishida, Tomoko; Toda, Shoichi; Kato, Hirotomo; Kimura, Hirokazu (Japanese Journal of Infectious Diseases, 2009)
This report describes multiple viruses in stool specimens from oyster-associated gastroenteritis. Eleven outbreaks of oyster-associated gastroenteritis were examined for enteric viruses between January 2002 and March 2006 in Japan. Multiple norovirus genotypes were detected in all outbreaks; moreover, kobuvirus, sapovirus, and astrovirus were also detected in 6, 3, and 1 of the 11 outbreaks, respectively. Notably, multiple sapovirus genogroups were detected in the stool specimens from subjects in two oyster-associated gastroenteritis outbreaks.